Antifungal activity of Calophyllum soulattri leaf extract on fungal isolate of coconut neera - Rachmani, Eka Prasasti Nur; Baroroh, Hanif Nasiatul; Rehana, Rehana; Rahmawati, Novia Ayu (Acta Pharmaciae Indonesia, 2022)
Background: Coconut neera is susceptible to fungus contamination. Some plants, such as Calophyllum soulattri, can function as natural preservatives with antifungal properties. Objective: This study aimed to evaluate the antifungal activity of C. soulattri leaf extract as measured by minimum inhibitory concentration (MIC) and minimum killing concentration (MKC). Methods: A dilution method was used to isolate the fungus that contaminated coconut neera. MIC and MKC antifungal activity were then evaluated using the liquid dilution method. Results: The results indicated that the contaminant fungi found in coconut neera belonged to the genus Penicillium. The MIC was 12.5%, while the MKC was 18.75%. Conclusion: C. soulattri leaf extract has the potential to be developed as an antifungals for food preservation.